Rapid adaptation to invasive predators overwhelms natural gradients of intraspecific variation - Melotto, Andrea (Nat Commun, 2020)
Invasive predators can exert strong selection on native populations. If selection is strong enough, populations could lose the phenotypic variation caused by adaptation to heterogeneous environments. We compare frog tadpoles prior to and 14 years following invasion by crayfish. Prior to the invasion, populations differed in their intrinsic developmental rate, with tadpoles from cold areas reaching metamorphosis sooner than those from warm areas. Following the invasion, tadpoles from invaded populations develop faster than those from non-invaded populations. This ontogenetic shift overwhelmed the intraspecific variation between populations in a few generations, to the point where invaded populations develop at a similar rate regardless of climate. Rapid development can have costs, as fast-developing froglets have a smaller body size and poorer jumping performance, but compensatory growth counteracts some costs of development acceleration. Strong selection by invasive species can disrupt local adaptations by dampening intraspecific phenotypic variation, with complex consequences on lifetime fitness.